The first description of the larva and pupa of crane fly genus Phyllolabis Osten Sacken, 1877 (Diptera, Limoniidae, Limnophilinae), with information for understanding the phylogenetic relationships and systematical position of the genus - Podeniene, Virginija; Gelhaus, Jon K. (Zootaxa, 2017)
Description, illustrations and habitat characteristics are given for the previously unknown last instar larvae and pupae of the genus Phyllolabis Osten Sacken, 1877 of the eastern palaearctic species Phyllolabis mongolica Podenas and Gelhaus, 2012 (Diptera: Limoniidae, Limnophilinae). Diagnostic features and phylogenetic relationships are discussed. Characters of the immatures stages of Phyllolabis shows similarities with the genus Austrolimnophila, Epiphragma and Dactylolabis and based on this investigation Phyllolabis is moved back into subfamily Limnophilinae s.l., albeit as one of its basal lineages.